Experimental Study Influences Changes In Compression Ratio To Performance Of Single Cylinder Otto Engine - Wibawa Endra Juwana; Rendy Adhi Rachmanto; Mugi Wiyono; Iwan Istanto (Mekanika: Majalah Ilmiah Mekanika, 2022)
Increasing the compression ratio is an attempt to increase the efficiency and performance of the engine. The purpose of the study was to analyze the effect of changes in the compression ratio on engine performance. Tests using a single-cylinder Otto engine by comparing the performance of an enlarged compression ratio of 9.7:1 and 10.4:1 with a standard compression ratio of 9.0:1. The result of the research is that the compression ratio of 9.7:1 produces a peak torque of 7.51 Nm at 6000 rpm, a peak power of 5.30 kW at 8000 rpm, and the lowest Brake-Specific Fuel Consumption (BSFC) is 0.146 kg/kWh at 6000 rpm. Torque and power increased by 0.09 Nm and 0.28 kW, and Brake-Specific Fuel Consumption (BSFC) decreased by 0.018 kg/kWh compared to the standard compression ratio of 9.0:1. Using a compression ratio of 10.4:1 produces a peak torque of 7.69 Nm at 6000 rpm, a peak power of 5.38 kW at 8000 rpm, and the lowest Brake-Specific Fuel Consumption (BSFC) is 0.116 kg/kWh at 6000 rpm. Torque and power increased by 0.27 Nm and 0.36 kW, and Brake-Specific Fuel Consumption (BSFC) decreased by 0.030 kg/kWh compared to the standard compression ratio of 9.0:1.